Understanding the explosion risk presented by ammonium nitrate and aluminium home-made explosives detonated as surface charges in hexahedral main charge containers - Collett, Gareth; Akhavan, Jacqueline; Critchley, Richard (Springer, 2024)
Ammonium nitrate and aluminium (AN–Al) has been used as a typical homemade explosive (HME) by non-state actors since the turn of the century. Despite the regulation applied to ammonium nitrate above 16% nitrogen content and an aluminium particle size below 200 µm, their use has been widespread in Afghanistan, Columbia, Iraq, Syria and Yemen. Containers used to utilise AN–Al as a man-portable improvised explosive device (IED) are typically hexahedral in shape, not the spherical or hemispherical geometries used to theorise risk mitigation. This is particularly important in post-blast investigation where explosives of a non-ideal nature are often used in non-spherical containers. Given the breadth of HME available to criminals, the explosion performance of forty hexahedral containers filled with AN–Al of unknown manufacture is examined. Performance of the AN–Al is determined through the surface detonation of these containers on alluvial soil, with apparent crater volume compared to theoretical calculations for spherical charges of TNT detonated in that same medium. A conversion factor for hexahedral main charges to spherical charges is then established to achieve more accurate predictions of the explosion risk using Kingery-Bulmash and Bowen curves. The paper provides worked examples for practical application and a methodology by which predictions of charge mass in other mediums such as asphalt can be determined.
Keywords: Home-made explosive; Crater; Hexahedral charge container; Alluvial soil; Asphalt